2007
DOI: 10.1063/1.2720391
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the partial photoionization cross sections and asymmetry parameters of S atoms in the photon energy range 10.0–30.0eV using constant-ionic-state spectroscopy

Abstract: The partial photoionization cross sections and asymmetry parameters of S atoms have been measured using constant-ionic-state ͑CIS͒ spectroscopy in the photon energy range 10.0-30.0 eV. The ionizations investigated in these CIS experiments are the ͑3p͒ −1 ionizations S + ͑ 4 S͒ ← S͑ 3 P͒, S + ͑ 2 D͒ ← S͑ 3 P͒, and S + ͑ 2 P͒ ← S͑ 3 P͒. For the first time Rydberg series which converge to the fourth ionization limit have been observed and assignments of these series have been proposed. These correspond to excitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 33 publications
4
16
0
Order By: Relevance
“…Their experimental work has already revealed the position of members of these resonance series. In the present study the first two members of the resonance series were observed at 17.82 ± 0.09 eV (69.57 ± 0.35 nm) and 19.02 ± 0.09 eV (65.19 ± 12.35 nm), respectively, which is in good agreement with the experimental work of Innocenti et al [77]. Our present theoretical estimates are also in respectable agreement with the present experimental work.…”
Section: Photoionization Of S(3ssupporting
confidence: 83%
See 4 more Smart Citations
“…Their experimental work has already revealed the position of members of these resonance series. In the present study the first two members of the resonance series were observed at 17.82 ± 0.09 eV (69.57 ± 0.35 nm) and 19.02 ± 0.09 eV (65.19 ± 12.35 nm), respectively, which is in good agreement with the experimental work of Innocenti et al [77]. Our present theoretical estimates are also in respectable agreement with the present experimental work.…”
Section: Photoionization Of S(3ssupporting
confidence: 83%
“…These features were also seen in the early theoretical work of Altun and co-workers [39]. These dip-like structures were first observed in this photon region by Innocenti and co-workers [77] using constant ionic state (CIS) spectroscopy. Innocenti and co-workers [77] showed that these window resonance originate from the 3s 2 3p 4 parent configuration and are due to the 3s → np excitation being members of the 3s3p 4 np Rydberg resonance series.…”
Section: Photoionization Of S(3ssupporting
confidence: 50%
See 3 more Smart Citations